2022
DOI: 10.1039/d2fo00595f
|View full text |Cite
|
Sign up to set email alerts
|

Fermented noni (Morinda citrifolia L.) fruit juice improved oxidative stress and insulin resistance under the synergistic effect of Nrf2/ARE pathway and gut flora in db/db mice and HepG2 cells

Abstract: Oxidative stress interferes with blood glucose homeostasis, leading to insulin resistance (IR) and hyperglycemia, which eventually induces type 2 diabetes (T2DM). Fermented noni (Morinda citrifolia L.) fruit juice (FNJ) is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 77 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Proteobacteria includes a mass of typical pathogens, such as Salmonella, Shigella, Klebsiella, and pathogenic Escherichia coli that can generate considerable toxins, thereby serving as a momemtous indicator of gut microbiota disturbance and health disorders of animals [44,45]. It has been documented that the expansions of Proteobacteria, Gammaproteobacteria, Enterobacteriales, Enterobacteriaceae, and Escherichia/Shigella in the gut could cause accumulation of lipopolysaccharide, rendering the occurrence of oxidative stress in animals [19,[46][47][48][49]. Herein, we detected negative correlations of the abundances of Proteobacteria, Gammaproteobacteria, Enterobacteriales, Enterobacteriaceae, and Escherichia/Shigella with both intestinal CAT activity and VH, demonstrating that the enrichments of these bacteria in the DON group conduced the simultaneous intestinal oxidative damage of broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Proteobacteria includes a mass of typical pathogens, such as Salmonella, Shigella, Klebsiella, and pathogenic Escherichia coli that can generate considerable toxins, thereby serving as a momemtous indicator of gut microbiota disturbance and health disorders of animals [44,45]. It has been documented that the expansions of Proteobacteria, Gammaproteobacteria, Enterobacteriales, Enterobacteriaceae, and Escherichia/Shigella in the gut could cause accumulation of lipopolysaccharide, rendering the occurrence of oxidative stress in animals [19,[46][47][48][49]. Herein, we detected negative correlations of the abundances of Proteobacteria, Gammaproteobacteria, Enterobacteriales, Enterobacteriaceae, and Escherichia/Shigella with both intestinal CAT activity and VH, demonstrating that the enrichments of these bacteria in the DON group conduced the simultaneous intestinal oxidative damage of broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Bioactive peptides from the cartilage protein hydrolysate of Mustelus griseus could protect H 2 O 2 -caused HepG2 cells from oxidative damage by increasing the levels of SOD, CAT, GPx, and glutathione reductase (GSH-Rx) and decreasing the content of MDA [22]. Zhang also reported that fermented noni (Morinda citrifolia L.) fruit juice (FNJ) markedly ameliorated oxidative stress damage by activating or resisting related antioxidant enzymes activities such as SOD, GPx, and MDA in insulin-resistant HepG2 cells [31]. Endogenous antioxidation defense systems that comprise the antioxidation enzyme recovery system and the glutathione system play a pivotal role in the resistance to oxidative stress.…”
Section: Cpw Counteracted the Oxidative Stress And Reinforced Antioxi...mentioning
confidence: 99%
“…Incorporating probiotic fermented herbs into the diet of grouper may enhance their Growth capacity and anti-oxidation ability, while also decreasing foregut lipase levels (Nie et al, 2022). Furthermore, researchers have revealed that fermented herbs could modify the intestinal oxidative stress and innate immunity in fish by altering the gut microbiota, regulating the gut barrier, and inflammatory response (Zhang et al, 2015;Park et al, 2016;Wang et al, 2021b;Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%